1999
DOI: 10.1037/0096-1523.25.2.518
|View full text |Cite
|
Sign up to set email alerts
|

Using eye height in different postures to scale the heights of objects.

Abstract: Four experiments examined eye height (EH) scaling of object height across different postures. In Experiment 1, participants viewed rectangular targets while they were standing, seated, and prone. Standing and seated judgments were similar, possibly due to EH scaling. Prone judgments were significantly lower, a result not attributable to the unfamiliarity of that posture (Experiment 2). In Experiment 3, shifts of seated EH produced height overestimations equivalent to those of standing viewers. Experiment 4 exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
65
3

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(81 citation statements)
references
References 17 publications
13
65
3
Order By: Relevance
“…If attended to, the texture information would have conflicted with EH information, thus reducing its effect. This hypothesis is supported by the results of recent studies on the effects of posture on perceived size (Wraga, 1999). Under monocular experimental conditions comparable with the present research, participants judged the height of rectangular targets in several postures, including seated, standing, and lying prone.…”
Section: Discussionsupporting
confidence: 80%
“…If attended to, the texture information would have conflicted with EH information, thus reducing its effect. This hypothesis is supported by the results of recent studies on the effects of posture on perceived size (Wraga, 1999). Under monocular experimental conditions comparable with the present research, participants judged the height of rectangular targets in several postures, including seated, standing, and lying prone.…”
Section: Discussionsupporting
confidence: 80%
“…The discrimination judgment is easier in panel C than in panel B, because the heights of the target poles differ categorically relative to eye height: One is taller, the other shorter used for scaling. This claim is consistent with research by Wraga (1999), who found that object height was scaled to EH when participants were seated and standing, but not when participants were lying on the ground. Additionally, individuals do not use EH to scale object height when they do not perceive themselves to be immersed in the scene.…”
Section: Eye-height Scaling In Perceptionsupporting
confidence: 81%
“…A = height from the observer's EH to the top of the object, B = observer EH, a = visual angle subtended by the top of the object to the observer's EH, and b = visual angle from the observer's EH to the ground. Adapted from Wraga (1999) Fig. 1 Three situations of varying difficulty for making relative height judgments.…”
Section: Eye-height Scaling In Perceptionmentioning
confidence: 99%
“…Since there are nonvisual sources of information for eye height [Wraga 1999], we eliminated texture on the hallway floors that would generate visible flow. In our displays, the only textured surfaces generating visible flow were the hallway walls.…”
Section: Visual Stimulusmentioning
confidence: 99%